Analysis of Family Health Problems Related to Groundwater Use around the Kebon Kongok Landfill, Lombok: A Cross-sectional Study - Idham Halid; Ajeng Dian Pertiwi; Didi Taswidi; Mohamad Sadli; Musparlin Halid; Dita Prihartini; Pauzan Pauzan; Suyitno Suyitno (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: The presence of landfills can threaten groundwater quality because the decomposition process of waste containing hazardous chemicals can cause surrounding groundwater pollution. As the amount of waste increases, the risk of environmental pollution around the landfill also increases, especially to groundwater sources used by the local community. The study aims to analyze family health problems related to the use of groundwater located near landfills. Methods: The study used a cross-sectional design around the Kebon Kongok landfill, West Lombok, West Nusa Tenggara (WNT), Indonesia. The sample amounted to 300 respondents who met the inclusion criteria. Data analysis was performed descriptively, chi-square test, and binary logistic regression by analyzing the adjusted odds ratio (AOR) results, p-value <0.05, and 95% confidence interval. Results: 164 respondents (54.7%) used well water for their daily needs. The results of the study based on binary logistic regression tests showed a significant relationship between history of diarrhea in children (p=0.002; AOR=3.65), nutritional status of the child (p=0.001; AOR=3.95), maternal history of fetal miscarriage (p<0.001; AOR=4.08), family history of skin disease (p=0.010; AOR=2.75), family history of ARI (p=0.011; AOR=2.72), disability status in the family (p<0.001; AOR=4.10), family history of chronic disease (p<0.001; AOR=4.79), history of mother giving birth to a low birth weight (LBW) infant (p=0.003; AOR: 2.97), and history of mother giving birth to a premature infant (p=0.009; AOR=2.64) with the use of groundwater in families around the landfill. Conclusions: Groundwater use near contaminated waste disposal sites is closely related to family health issues related to diarrhea, nutritional status, fetal miscarriage, skin diseases, ARI, disability, chronic diseases, LBW, and history of mother giving birth to a premature infant. This indicates the need for significant health and environmental interventions to protect surrounding communities from the health risks of using polluted groundwater.